2021
DOI: 10.1177/25161032211053340
|View full text |Cite
|
Sign up to set email alerts
|

Youth, prosociality, and child welfare: an investigation of positive peer influence and youth prosocial behavior in group home care

Abstract: Only a limited number of studies have investigated the association between positive peer influence and youth prosocial behavior in child welfare. None of such studies has been completed in group home setting for youth. This study aimed to examine if positive peer influence is associated with (or predicts) youth prosocial behavior. The Ontario Looking After Children (OnLAC) database was used for analysis. There were 875 participants (males and females) aged 10 to 17 who were surveyed in group homes in 2010–2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…The study revealed that peer influence stimulated the concept of building moral values in the surrounding areas, collectively giving rise to an innovative social system prevailing on the principles of moral values. This finding is consistent with that of Joseph and Kuperminc ( 2021 ) and Osei ( 2021 ), indicating that peer influence plays a vital role observed prosocial behavior among individuals and groups.…”
Section: Discussionsupporting
confidence: 92%
“…The study revealed that peer influence stimulated the concept of building moral values in the surrounding areas, collectively giving rise to an innovative social system prevailing on the principles of moral values. This finding is consistent with that of Joseph and Kuperminc ( 2021 ) and Osei ( 2021 ), indicating that peer influence plays a vital role observed prosocial behavior among individuals and groups.…”
Section: Discussionsupporting
confidence: 92%